Using Machine Learning to Analyze the Learning Process for Solving Mathematical Problems - Bauyrzhan , Nauryzbayev; Sakysh , Baygamitova; Zhanar, Akhmetova; Nikolay, Pak; Ardak , Karipzhanova; Kumys, Urazbaeva (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The relevance of the research under consideration is due to the need to improve the efficiency of the analysis of the quality, and completeness of the knowledge obtained by students when solving computational problems, the example problems in mathematics. The theoretical argumentation is proposed and the practical implementation of an intelligent automated analytical system for analyzing the quality and forecasting the content of educational material and the trajectories of the student’s learning direction is described. The relevance of the research is the creation of neural network algorithms that allow analyzing the dynamics of changes in the student’s level of formation of skills to solve arithmetic problems. The methods of analyzing the assimilation of educational information and methods of personalized construction of the curriculum for each student are substantiated.